Bacteriological study of Turag river - Islam, Tasnim; Islam, Marzana; Mim, Tasmia Jahin; Promi, Fariha Ahsan (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2023.